2018
DOI: 10.15611/pn.2018.523.18
|View full text |Cite
|
Sign up to set email alerts
|

Megatrends and their use in economic analyses of contemporary challenges in the world economy

Abstract: The objective of the article was to perform a literature review to analyze the use of megatrends as an analytical framework in various areas of economic and social discourse. Following SALSA methodology, the scope of the research covers peer reviewed articles published between 2010 and 2018. The results show that the concept of megatrends has been utilized in analyzing the impact of fundamental economic and social changes in three main areas: foresight studies of selected industries, analyses of existing and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…The need to expand the review and include a variety of publications (e.g. reports by consulting companies) was identified as a research opportunity in the literature review conducted by Malik and Janowska 2018 . Based on a systematic literature review and a workshop, a total of 23 megatrends (M) and 72 related trends (T) were identified as the summary in Table 7 shows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to expand the review and include a variety of publications (e.g. reports by consulting companies) was identified as a research opportunity in the literature review conducted by Malik and Janowska 2018 . Based on a systematic literature review and a workshop, a total of 23 megatrends (M) and 72 related trends (T) were identified as the summary in Table 7 shows.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the studies mentioned above, consulting firms such as EY, PWC and KPMG have explored megatrends by frequently mentioning demographic shifts, geopolitical changes and environmental impacts as key megatrends. These studies lack comprehensive and coherent understanding of megatrends with political, economic or social megatrends being the center of attention (Malik and Janowska 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of a structured literature review covering research articles published between 2010 and 2018, the reference frequency and thematic application of megatrends have been established (Malik and Janowska, 2018). In the studied set of research papers, the concept of megatrends was frequently used to analyze the impact of the most profound ones on selected research areas, whose thematic scope can be divided into three general categories: foresight studies of selected industries, analyses of existing and anticipated changes in management and business practices, as well as other socio-economic topics.…”
Section: Megatrends In Economic Analysesmentioning
confidence: 99%
“…The content of the most frequently used megatrends includes: technology development, environmental changes, demographic shifts, urbanization and changes in geopolitics. The results of the literature review (Malik and Janowska, 2018) made it possible to single out the seven preeminent megatrends most frequently referred to and relatively coherently defined by the authors, they are: 1) digitalization and development of ICT technologies (later digitalization), 2) resource scarcity, 3) climate change, 4) world population growth (later population growth), 5) population aging, 6) urbanization growth.…”
Section: Megatrends In Economic Analysesmentioning
confidence: 99%
“…Many economists believe the economy is currently undergoing quite fundamental changes (Leceta et al, 2017;Malik, Janowska, 2018;Rifkin, 2014;Rifkin, 2001;Scholz, 2013;Tapscott, 2014). The changes affect many spheres of human life.…”
Section: Introductionmentioning
confidence: 99%